Hambatan Implementasi Sisrute Dalam Optimalisasi Penanganan Kasus Kedaruratan Obstetri - Makmur, Muh. Ismail (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The Integrated Referral Information System (SISRUTE) digital platform was developed by the Indonesian Ministry of Health as an innovative solution to optimize referral mechanisms between healthcare facilities. However, its implementation faces substantial challenges, particularly in managing obstetric emergencies that require rapid and highly precise responses. This study analyzes the fundamental obstacles in the operationalization of SISRUTE and its impact on the efficiency and effectiveness of emergency maternal referrals. The research employs a descriptive-qualitative methodology, incorporating comprehensive literature review and in-depth interviews with healthcare practitioners at referral institutions. The findings indicate that the primary issues stem from the technical dimensions of the platform, misalignment in the capacity of referral institutions, limitations in human resources, and suboptimal inter-facility coordination.